Moderating Role of Audit Fees on the Effect of Task Complexity and Independence towards Audit Judgment - Nur Eny; Ratna Mappanyukki (Universitas Hayam Wuruk Perbanas, 2020)
This study examines the effect of task complexity and auditor independence on audit judgment with audit fees as a moderating variable. Samples were obtained from auditors working in public accounting firms in West Jakarta and South Jakarta. Data collec-tion was done using a survey method by distributing questionnaires to 100 auditors as respondents. The method of analysis used was Moderated Regression Analysis. The results show that task complexity hurts audit judgment. Auditor independence has a positive effect on audit judgment. Audit fees can strengthen the effect of task complexity on audit judgment. Besides, audit fees moderate the effect of auditor independence on audit judgment. It is recommended that public accounting firms consider the inter-action of variables that affect audit judgment, such as task complexity, independence, and audit fees, to improve audit quality.